Selective list of the Catalogues of the VIR Global Collection of cereal crops: oat, rye, and barley, for 1964-2021 - article Editorial (Труды по прикладной ботанике, генетике и селекции)
Catalogues of the VIR Global Collection of cereal crops: oat, rye, and barley, for 1964-2021.